Presence of the Coxsackievirus and Adenovirus Receptor (CAR) in human neoplasms: A multitumour array analysis - Reeh, M.; Bockhorn, M.; Görgens, D.; Vieth, M.; Hoffmann, T.; Simon, R.; Izbicki, J. R.; Sauter, G.; Schumacher, U.; Anders, M. (British Journal of Cancer, 2013)
Background:The Coxsackie-and Adenovirus Receptor (CAR) has been assigned two crucial attributes in carcinomas: (a) involvement in the regulation of growth and dissemination and (b) binding for potentially therapeutic adenoviruses. However, data on CAR expression in cancer types are conflicting and several entities have not been analysed to date.Methods:The expression of CAR was assessed by immunohistochemical staining of tissue microarrays (TMA) containing 3714 specimens derived from 100 malignancies and from 273 normal control tissues.Results:The expression of CAR was detected in all normal organs, except in the brain. Expression levels, however, displayed a broad range from being barely detectable (for example, in the thymus) to high abundance expression (for example, in the liver and gastric mucosa). In malignancies, a high degree of variability was notable also, ranging from significantly elevated CAR expression (for example, in early stages of malignant transformation and several tumours of the female reproductive system) to decreased CAR expression (for example, in colon and prostate cancer types).Conclusion:Our results provide a comprehensive insight into CAR expression in neoplasms and indicate that CAR may offer a valuable target for adenovirus-based therapy in a subset of carcinomas. Furthermore, these data suggest that CAR may contribute to carcinogenesis in an entity-dependent manner. © 2013 Cancer Research UK.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Coxsackievirus and Adenovirus receptor; differential expression; multitumour tissue microarray